CENTRAL KALIMANTAN PROVINCE ANALISIS KEBIJAKAN PENGEMBANGAN KOMODITI JAGUNG DI PROVINSI KALIMANTAN TENGAH (STUDI KASUS DESA NGURIT KECAMATAN GUNUNG BINTANG AWAI KABUPATEN BARITO SELATAN) - Hakim, Arief Rahman (JURNAL SOCIOPOLITICO, 2024)
One of the policies of the Central Kalimantan Provincial Government is the development of corn commodities in South Barito Regency. This research will try to analyze and evaluate the implementation of this policy, especially in terms of corn production and increasing farmers' income. The research was carried out in Ngurit Village, Gunung Bintang Awai, District South Barito Regency. Research respondents consisted of 30 corn farmers and 5 traders/collectors. Data collection was carried out through an interview and observation process. The research results show that the corn commodity development policy in South Barito Regency has succeeded in increasing corn production and farmer income. The research results showed that corn production increased by 1,200 tons/planting season in the form of wet shelled corn (moisture content 29-30%) with an average productivity of 3 tons/ha/planting season. Financially, corn farming is also profitable for farmers. This is shown by the R/C ratio of 1.875, meaning that every investment of IDR 1 will generate income of IDR 1,875. The B/C ratio value for corn farming at the research location (87.5%) is also higher than the average interest rate on bank deposits, meaning that the funds used to carry out corn farming provide greater income than if the funds were kept in a bank. The corn trading system in the research village has been running efficiently. This can be seen from the very short corn marketing chain, which only involves farmers-traders/collectors-factories. The marketing efficiency value (20.48%) and marketing margin (54.95%) show that the corn trading system has also run efficiently, meaning that not too many costs are absorbed in the marketing system and farmers still get the largest portion in the corn trading system.